Childhood triglyceride-glucose index and pre-hypertension in adulthood: a prospective cohort study - Zhao, Lingli; Cui, Zhijie; Ouyang, Jiahui; Qu, Hua; Gao, Zhuye (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride-glucose (TyG) index serves as a surrogate marker for insulin resistance. Multiple studies have demonstrated a positive correlation between the TyG index and blood pressure, indicating that a high TyG index is related to a greater risk of developing pre-hypertension (pre-HTN) and hypertension (HTN). However, the relationship between changes in the TyG index during childhood and pre-HTN in adulthood requires further clarification.MethodsThe present prospective study utilized data from the Bogalusa Heart Study, a long-term follow-up study. Data on triglycerides (TG), fasting glucose (Fg), and low-density lipoprotein cholesterol (LDL-C) were collected from cross-sectional examinations of participants during childhood. Blood pressure (BP) in early adulthood was categorized into normotensive and pre-HTN groups. Logistic regression was employed to evaluate the relationship between the TyG index in childhood and pre-HTN in adulthood.ResultsA total of 1,222 participants were included in the study, of whom 258 presented with pre-HTN in adulthood. Significant differences were observed in baseline TyG index, body mass index (BMI), and high-density lipoprotein cholesterol (HDL-C) between the two groups. In both unadjusted logistic regression (Odds Ratio (OR):1.8, 95% CI: 1.4, 2.5, P < 0.001) and simple adjustment (OR: 1.7, 95% CI: 1.2, 2.3, P = 0.003), childhood TyG index were significantly associated with pre-HTN in adulthood. However, this significant relationship disappeared after full adjustment (OR: 1.2, 95% CI: 0.8, 1.9, P = 0.373) which extended Model 1 by including adjustments for baseline BMI, baseline HDL-C, baseline LDL-C, smoking status, drinking status, use of antihypertensive medication and family history of HTN.Stratified analysis in Model 2 showed that gender and race significantly affected the relationship between TyG index and BP. In the male population, elevated TyG index levels increased the probability of pre-HTN, whereas no such relationship was found in female (Male: OR: 1.9, 95% CI: 1.1, 3.5, P = 0.029; Female: OR: 0.8, 95% CI: 0.4, 1.4, P = 0.447; P for interaction = 0.037). Similarly, in American Caucasians, TyG was positively associated with the risk of pre-HTN, but this relationship was not observed in African American (American Caucasian: OR: 1.7, 95% CI: 1.0, 2.9, P = 0.035; African American: OR: 0.5, 95% CI: 0.2, 1.1, P = 0.087; P for interaction = 0.007).ConclusionsIn males and Caucasians, elevated TyG index during childhood can increase the risk of pre-HTN in adulthood. Monitoring the TyG index may help in screening individuals at higher risk of pre-HTN.